Pengaruh Pemberian Aromaterapi Jahe Terhadap Kejadian Emesis Gravidarum Pada Ibu Hamil Trimester I di PMB A Klapanunggal Bogor Tahun 2022 - M Haikal Dimas Adrianto; Nurul Ainul Shifa (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Nausea and vomiting induced by emesis gravidarum typically do not result in maternal fatality; nevertheless, they may give rise to malnutrition and dehydration due to challenges in consuming food and beverages. Ginger, recognized as a longstanding spice, offers a range of advantages. In addition to its usage as a culinary seasoning, beverage ingredient, and confectionery, ginger is also employed in traditional medicinal concoctions. This study seeks to juxtapose the outcomes preceding and following the administration of ginger aromatherapy to expectant mothers in their first trimester. The methodology employed in this research is experimental in nature, specifically adopting a quasi-experimental blueprint involving a pre-test and post-test configuration without a control cohort. The study cohort encompasses 30 initial trimester expectant mothers grappling with emesis gravidarum, who attended prenatal care at PMB A Klapanunggal. Derived from the outcomes of the 2022 inquiry into the Impact of Ginger Aromatherapy on Emesis Gravidarum Incidence in Pregnant Women at PMB A Klapanunggal Bogor, it can be deduced that a notable distinction exists in the frequency of emesis gravidarum prior to and subsequent to the application of ginger aromatherapy to first-trimester expectant mothers (Two-tailed Sig = 0.000 < 0.005). Furthermore, the expectant mothers comprehended and executed the insights on ginger aromatherapy dispensed by the researcher, proficiently integrating complementary therapy into their domestic routines. Consequently, healthcare establishments are advised to impart awareness regarding the adoption of non-pharmacological treatments, including aromatherapy, which are conveniently accessible and viable for initial trimester expectant mothers.